How to Measure the Fiscal Deficit. (International Monetary Fund, 1991)
Fiscal policy seeks to equilibrate the public sector's financing needs with the private sector's demand for investment and a sustainable balance of payments. Correct measurement of the public sector's net use of resources is therefore an important prerequisite for managing the macroeconomy. This volume, edited by Mario I. Blejer and Adrienne Cheasty, is organized around four issues: the adequacy of summary measures of the fiscal deficit, conventional and adjusted deficits, coverage (size) of the public sector, and the public sector's intertemporal budget constraint.